Cumulative exposure to melphalan chemotherapy and subsequent risk of developing acute myeloid leukemia and myelodysplastic syndromes in patients with multiple myeloma. (28th May 2021) - Jonsdottir, Gudbjorg; Björkholm, Magnus; Turesson, Ingemar; Hultcrantz, Malin; Diamond, Benjamin; Porwit, Anna; Landgren, Ola; Kristinsson, Sigurdur Y.
Abstract: Objectives: The aim of this study was to determine risk factors for development of acute myeloid leukemia/myelodysplastic syndromes (AML/MDS) in patients with multiple myeloma (MM). Methods: We identified all patients diagnosed with MM in Sweden from January 1st, 1958 to December 31, 2011. A total of 26 627 patients were diagnosed with MM with during the study period. Of these, 124 patients (0.5%) developed subsequent AML/MDS. For each patient with MM and a subsequent AML/MDS diagnosis, we randomly selected a matched (age, sex, and date of MM diagnosis) MM patient without a subsequent second malignancy diagnosis. Results: The cumulative melphalan exposure was significantly higher (OR = 2.8, 95% CI 1.7‐5.2; P < .001) among cases (median 988 mg; IQR 644‐1640) compared with controls (median 578 mg; IQR 360‐967). Median time to AML/MDS development was 3.8 years (IQR 2.8‐5.8). Risk of AML/MDS was not statistically altered by M protein isotype, anemia, renal failure, hypercalcemia, lytic bone lesions, or radiation therapy. Conclusion: In this nationwide population‐based study, we show that increased cumulative doses of alkylating therapy with melphalan increases the subsequent risk of developing AML/MDS in patients with MM. Given improved survival in MM patients over the last decade future studies will be important to better define long‐term risks.